TCMIP v2.0 Powers the Identification of Chemical Constituents Available in Xinglou Chengqi Decoction and the Exploration of Pharmacological Mechanisms Acting on Stroke Complicated With Tanre Fushi Syndrome - Wang, Ping; Wang, Shuang; Chen, Hong; Deng, Xiaofang; Zhang, Luoqi; Xu, Haiyu; Yang, Hongjun (Frontiers in Pharmacology, 2021)
Xinglou Chengqi (XLCQ) decoction, composed of three botanical drugs and one inorganic drug, are used in clinic during the treatment of acute stroke complicated with Tanre Fushi (TRFS) syndrome in China. However, its active ingredients and molecular mechanism have not been clarified. So, we aimed to preliminarily character its chemical constituents and investigate its pharmacological mechanisms using integrative pharmacology strategy, including component analysis, network prediction and experimental verification. We employed UPLC-QTOF-MS/MS to describe the chemical profile of XLCQ, Integrative Pharmacology-based Network Computational Research Platform of Traditional Chinese Medicine (TCMIP v2.0, http://www.tcmip.cn/) to assist identifying the chemical components and predict the putative molecular mechanism against acute stroke complicated with TRFS, and LPS-stimulated BV-2 cells to verify the anti-neuroinflammatory effects of luteolin, apigenin and chrysoeriol. Altogether, 197 chemical compounds were identified or tentatively characterized in water extraction of XLCQ, 22 of them were selected as the key active constituents that may improve the pathological state by regulating 27 corresponding targets that mainly involved in inflammation-immune related pathways, and furthermore, luteolin, apigenin and chrysoeriol exhibited good anti-neuroinflammatory effects from both protein and mRNA levels. In summary, it is the first time to employ integrative pharmacology strategy to delineate 22 constituents that may improve pathological state of stroke with TRFS by regulating 27 corresponding targets, which may offer a highly efficient way to mine the scientific connotation of traditional Chinese medicine prescriptions. This study might be a supplement for the deficiency of the basic research of XLCQ.